(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper aims to analyze Law no. 193/2023 contents to take into consideration the characteristics of the new right to be forgotten for cancer survivors, the constitutional principles it expresses, and its capability to pursue full social and economic reintegration of those who recovered from an oncological pathology, by ending its subsequent discrimination.